Comparison Between Manipulation Under Anaesthesia and Intra-Articular Steroid Injections for Frozen Shoulder - MuhammadImranButt,ToobaIqbal,ShahzadAnjum, MuhammadImranButt,ToobaIqbal,ShahzadAnjum, (Journal of Rawalpindi Medical College, 2018)
Background: To compare the outcome between manipulation under anaesthesia (MUA) and intra-articular steroid injections in the shoulder, for patients diagnosed with frozen shoulder (adhesive capsulitis), within a short follow up period. Methods: In this randomized control trial 140 patients with primary frozen shoulder were included. Patients that had been injected with steroid in the frozen shoulder already, and those with comorbidities such as diabetes, were excluded. Patients were randomized into two groups, manipulation under anaesthesia (MUA) or intra articular steroid injection. All patients were reviewed at 04 weeks with each patient completing the shoulder pain and disability index Score along with the Visual Analogue Sale (VAS) score to assess pain levels at follow-up. Results: Mean age was 51.13 + 6.84 years. The ratio of female to male was 1:3. Mean pain score is decreased significantly from 3.33 ± 1.10 before intervention to 2.25 ± 0.78 (SD) and mean disability index score dropped from 5.85 ± 1.46 before intervention to 2.46 ± 0.72 , after intervention (p-value <0.001). There was no significant difference between the time within which pain was reduced or function of the shoulder was improved. Conclusion: Given the cost implications and the potential risks of manipulation under anaesthesia , it is recommended to use steroid injections as a preferable treatment option over MUA and physiotherapy as the primary treatment option during the freezing phase of adhesive capsulitis